Dysphagia in healthy children: Characteristics and management of a consecutive cohort at a tertiary centre. (August 2017) - Svystun, Orysya; Johannsen, Wendy; Persad, Rabin; Turner, Justine M.; Majaesic, Carina; El-Hakim, Hamdy
Abstract: Objective: Whereas the literature is replete with reports on complex children with dysphagia (DP), the parameters characterizing non-neurologically impaired (NNI) children have been underreported, leaving a substantial knowledge gap. We set to characterize a consecutive cohort of NNI children, their management, and outcomes. Methods: We undertook a retrospective case series. Children (<18 years old) attending a tertiary multidisciplinary swallowing clinic were eligible. Patients with neuro-developmental, neuromuscular, or syndromic abnormalities were excluded. Primary outcomes included demographics, co-morbidities, presentations, McGill score, swallowing and airway abnormalities (and their predictors). Secondary outcomes were interventions and management response. Results: From 171 consecutive patients (37-month period), 128 were included (69 males, median age 6.6 months (0.5–124.2)). Significant clinical presentations included recurrent pneumonias (20), cyanotic spells (14) and life-threatening events (10). Swallowing assessments revealed laryngeal penetration (67), aspiration (25). Other investigations included overnight oximetry (77), airway (70), and gastrointestinal endoscopy (24); revealing laryngomalacia (29), laryngeal mobility disorder (8), and subglottic stenosis (8). Non-surgical interventions involved oral diet modifications (85) and enteral nutrition (15). Surgical interventions included supraglottoplasties (18), endoscopic laryngeal cleft repair (14), and injection (19). 119 patients received intervention and at last follow-up (median 5.2 months (0.3–88.8)) 94 had improved. Of those treated 116 were on an unmodified oral diet, and 24 on a modified diet. ALTE and snoring predicted airway abnormalities, recurrent pneumonia predicted swallowing abnormalities, and age and airway lesions predicted the McGill score. Conclusion: a significant proportion of NNI children with DP harbor airway and swallowing abnormalities warranting endoscopic and instrumental assessment.